Short-Term Outcomes of COVID-19 Pandemic on Non-Small Cell Lung Cancer Screening and Management - Orelaru, Felix; Edwards, Melanie; Raleigh, Ruth; Abunayla, Ali; Bush, Rachel; Porter, Shannon; Schumaker, Kate; Albright, Jeremy; Adams, Kumari N. (The Surgery Journal, 2023)
Background To assess the impact of coronavirus disease 2019 (COVID-19) pandemic on non-small cell lung cancer (NSCLC) screening, staging, and management in a single health care system.Materials and Methods From November 2015 to December 2020, a total of 1,547 NSCLC cases was reported at our institution including 1,329 cases pre-COVID-19 and 218 cases during COVID-19. Pre-COVID-19 was defined as November 2015 to February 2020, while during COVID-19 was March 2020 to December 2020. Data were collected from tumor registry and medical record review. Patients with mesothelioma, lymphoma, small cell, or mixed small cell cancer were excluded from the study.Results Both pre-COVID-19 and during COVID-19 cohorts had similar comorbidities including age (70 vs. 71 years), current smokers (35 vs. 32%), and chronic obstructive lung disease (32 vs. 28%). The number of low-dose computed tomography lung cancer screening scans decreased by 25% during COVID-19 compared with pre-COVID-19 era. There were more cases of stage 1A NSCLC pre-COVID-19 (31 vs. 25%) and more stage 4 cancer during COVID-19 (42 vs. 33%); p = 0.01. The proportion of patients treated with radiotherapy was similar between pre-COVID-19 and during COVID-19 (49 vs. 50%), but fewer patients underwent surgery during COVID-19 (17 vs. 27%; p = 0.004). The median time to radiotherapy (67 days) and surgery (29 days) was similar between the groups. The unadjusted overall 6-month mortality after lung cancer diagnoses was higher during COVID-19 compared with pre-COVID-19 (28 vs. 22%; p = 0.04).Conclusion The COVID-19 pandemic resulted in delayed lung cancer screening scans, and more patients had diagnosis of advanced NSCLC; however, short-term mortality was unchanged.
Keywords: COVID-19; non-small cell lung cancer; radiotherapy; surgical management